The Effectiveness of Islamic Education Learning Based on Learning Cycle on Learning Outcomes in Junior High School: Efektivitas Pembelajaran PAI Berbasis Learning Cycle Terhadap Hasil Belajar di SMP - Moch Risal; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2021)
Education has the task of creating quality human beings who are able to compete, especially preparing students who are independent, creative and innovative. One of the successes of students in learning can be seen from the suitability of the learning model applied by the teacher. One model of constructivism is the learning cycle, which is a student-centered model. This learning allows students to observe but can also draw conclusions about the concepts being studied. The purpose of this study was to determine the implementation of the Learning Cycle learning model on the subject of the Development of Science in the Abassiyah Period. This research was divided into 2 cycles, namely Cycle I and Cycle II. The type of research is Classroom Action Research. The research design used in this research is action research. The data analysis technique in this research is descriptive statistics. The results of the study indicate the effectiveness of learning using the 5E learning cycle model on student learning outcomes. Cycle II is a very effective cycle when using a supporting instrument in the form of mind maps. The percentage of students reached 97% exceeding the school's minimum passing standard (KKM) of 75. Students became more active, creative, and able to work well together.